2017
DOI: 10.1161/strokeaha.116.014335
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Locations, and Longitudinal Course of Cerebral Microbleeds in European Moyamoya

Abstract: Background and Purpose-Cerebral microbleeds (cMBs) have previously been linked with especially high incidence in Asian patients with moyamoya together with high tendency to bleed. This, presumably, is characteristic of patients with moyamoya. Herein, we, therefore, investigate retrospectively the frequency, location, and longitudinal course of cMBs in a large German cohort. Methods-We included all patients with moyamoya who underwent standard magnetic resonance imaging, including T2*-weighted images, in our de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…This distribution pattern corresponds to that described in a past study that investigated bleeding using acute-phase CT 12 and also resembles the distribution of microbleeds in Moyamoya disease. 10,11 Furthermore, the choroidal artery was most frequently detected as the responsible vessel in the periventricular area. Previous studies have shown dilation of the choroidal artery and posterior communicating artery as risk factors for ICH in Moyamoya disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This distribution pattern corresponds to that described in a past study that investigated bleeding using acute-phase CT 12 and also resembles the distribution of microbleeds in Moyamoya disease. 10,11 Furthermore, the choroidal artery was most frequently detected as the responsible vessel in the periventricular area. Previous studies have shown dilation of the choroidal artery and posterior communicating artery as risk factors for ICH in Moyamoya disease.…”
Section: Discussionmentioning
confidence: 99%
“…Although some reports have investigated the distribution of microbleeds in Moyamoya disease, 10,11 no reports have addressed the bleeding point and vessels responsible for symptomatic hemorrhage related to Moyamoya disease, with the exception of 1 study using head CT. 12 Determining the site from which bleeding has occurred on CT and MR imaging performed during acutephase hemorrhage is often difficult.…”
mentioning
confidence: 99%
“…The sequence is exquisitely sensitive to areas of chronic microhemorrhage, which are seen with an increased incidence in MMD and may be associated with increased risk of intracranial hemorrhage. 29,56,72 The brush sign of prominent deep medullary veins on SWI may be associated with likelihood of infarct, low cerebral blood flow (CBF), and low CVR. 22 Asymmetrically prominent superficial cortical vessels on SWI are associated with elevated deoxyhemoglobin content with increased oxygenation extraction; with revascularization, this finding may reverse and may predict potential to improve CBF.…”
Section: Fig 1 a And Bmentioning
confidence: 99%
“…53 CMBs, located in deep and periventricular regions, are seen in 28-46% of cases although a recent report concerning a European moyamoya patient cohort found a lower prevalence of 12.9%. [54][55][56] Their presence is associated with dilated anterior choroidal or posterior communicating arteries. Periventricular CMBs increase the risk of intraventricular hemorrhage.…”
Section: Moyamoya Diseasementioning
confidence: 99%